AN ANALYSIS OF STUDENTS’ LANGUAGE LEARNING STRATEGIES IN ACADEMIC WRITING - Restu Winarsih; Urai Salam; Dwi Riyanti (Universitas Suryakancana, 2021)
This research was aimed to investigate students’ writing strategies in enhancing their English academic writing skills. This case study interviewed two students from English Department to reveal students’ strategies in academic writing. The data were collected using semi-structured interviews and document reviews. The findings showed that the two students who categorized as good language learners in writing skills employed all five writing strategies as proposed by Mu (2005) in their writing process. The data showed that metacognitive strategies and social/affective strategies were used most by the students. The strategies were organizing strategies, resourcing, setting goals, reviewing and editing, and avoidance strategies. The data also indicated that the two students were not achieving the goal of learning instantly. They employed strategies effectively in their individual learning in enhancing their writing skills.